1996
DOI: 10.1063/1.362953
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of phonon-limited mobility of two-dimensional electrons in strained and unstrained Si metal–oxide–semiconductor field-effect transistors

Abstract: The phonon-limited mobility of strained Si metal–oxide–semiconductor field-effect transistors (MOSFETs) fabricated on a SiGe substrate is investigated through theoretical calculations including two-dimensional quantization, and compared with the mobility of conventional (unstrained) Si MOSFETs. In order to match both the mobility of unstrained Si MOSFETs and the mobility enhancement in strained Si MOSFETs, it is necessary to increase the coupling of electrons in the two-dimensional gas with intervalley phonons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
210
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 451 publications
(228 citation statements)
references
References 20 publications
7
210
1
5
Order By: Relevance
“…The strain changes the electronic band structure resulting in the change of carrier mobility [1][2][3][4][5]. While the electrostatics of strained MOSFETs has been studied, several research groups have reported the mobility characteristic in strained MOSFETs [1,6] or in unstrained MOSFETs [7,8]. It is also reported that the intervalley phonon scattering is required to accurately explain the behavior of inversion layer mobility in both strained and unstrained Si MOSFETs [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The strain changes the electronic band structure resulting in the change of carrier mobility [1][2][3][4][5]. While the electrostatics of strained MOSFETs has been studied, several research groups have reported the mobility characteristic in strained MOSFETs [1,6] or in unstrained MOSFETs [7,8]. It is also reported that the intervalley phonon scattering is required to accurately explain the behavior of inversion layer mobility in both strained and unstrained Si MOSFETs [9].…”
Section: Introductionmentioning
confidence: 99%
“…F i,j is the form factor determined by the wave functions of the i th and the j th subbands [6]. The momentum relaxation rate for intervalley phonon scattering (τ i inter ) from the i th subband to the j th subband is given by…”
Section: Mobility Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10] A 2D model is appropriate in the case that electronic coupling in the direction perpendicular to stacked lamellae is negligible. This is the case for polymers such as P3HT and PBTTT, where the lamellae are separated by electronically insulating alkyl chains.…”
mentioning
confidence: 99%